SEPARATION OF NICKEL AND COBALT IN SOLUTION FROM MIXED HYDROXIDE PRECIPITATE (MHP) LEACHING BY SOLVENT EXTRACTION USING VERSATIC 10 FOLLOWED BY CYANEX 272 - Dartwin
lithium ion batteries, nickel and cobalt from nickel laterite ores are commonly prepared in the form of nickel sulfate and cobalt sulfate through leaching, purification of the pregnant leach solution, separation of nickel and cobalt and crystallization of both metals in the form of nickel sulfate and cobalt sulfate hexahydrate. The separation of nickel and cobalt is usually carried out by the solvent extraction (SX) method in a mixed hydroxide precipitate (MHP) or mixed sulfide precipitate (MSP) solution. In this study, the separation of nickel and cobalt in the solution produced by MHP leaching was carried out by SX using Versatic 10 followed by Cyanex 272 and studied the effect of various SX process variables on the extraction of nickel and cobalt and the separation factor between the two (????Co- Ni) and the separation factor with metals. impurities (Mg and Ca). The pregnant leach solution was prepared by atmospheric agitation leaching of limonite ore followed by iron precipitation, MHP precipitation, MHP re-leaching, and SX. The SX experiment was designed with 4 variables, each of which was varied at a certain level. A series of SX experiments were conducted to study the effects of SX time, initial pH, ratio of organic volume to aqueous (O/A ratio), and concentration of extractant to extraction percentage of nickel and cobalt as well as separation factor between nickel and cobalt and separation factor of the two metals with impurities (Mg and Ca). The concentration of nickel and cobalt in aqueous solution was measured using Atomic Absorption Spectroscopy (AAS). The results of experiment of the extraction stage of SX using Versatic 10 show that The results of the SX experiment using Versatic 10 show that the effect of increasing the processing time tends to increase the extraction percentages of nickel and cobalt up to a certain level, which then decreases if it exceeds this time limit, while the effect of increasing the initial pH, O/A ratio, and extractant concentration tends to increase the extraction percentages of nickel and cobalt. The best conditions for SX using Versatic 10 were obtained with a time of 10 minutes, initial pH 7.0, O/A ratio 0.50, and an extractant concentration of 20% with ????Ni-Mg and ????Co- Mg of 2526.02 and 647.93 respectively, and ????Ni-Ca and ????Co-Ca of 66.90 and 17.19, respectively. The results of the SX experiment using Cyanex 272 showed that increasing time tends to increase the extraction percentage of cobalt until a certain value and decrease if it exceeds this time limit, while increasing the initial pH, O/A ratio, and extractant concentration tends to increase the extraction percentage of cobalt. The best condition of SX using Cyanex 272 was obtained at a time of 10 minutes, initial pH 5.5, O/A ratio 0.75, and extractant concentration of 15% with ????Co-Ni of 3871.29.